Survival of AIDS patients in the Southeast and South of Brazil: analysis of the 1998-1999 cohort Sobrevida de pacientes com AIDS das regiões Sudeste e Sul do Brasil: análise da coorte de 1998 a 1999 - Ione Aquemi Guibu; Marilisa Berti de Azevedo Barros; Maria Rita Donalísio; Ângela Tayra; Maria Cecília Goi Porto Alves (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The aim of this study was to evaluate survival time for AIDS patients 13 years and older in the South and Southeast regions of Brazil, according to socio-demographic, clinical, and epidemiological characteristics. The sample was selected from all cases diagnosed in 1998 and 1999 and notified to the Epidemiological Surveillance System of the National STD/AIDS Program. Use of a questionnaire allowed analyzing 2,091 patient charts. Based on the Kaplan-Meier method, estimated survival was at least 108 months after diagnosis in 59.5% of patients in the Southeast and 59.3% in the South. Cox regression models showed, in both regions, an increase in survival in patients on antiretroviral therapy, those classified as AIDS cases according to the CD4 T-cell criterion, females, and those with more schooling. Other factors associated with longer survival in the Southeast were: white skin color, no history of tuberculosis since the AIDS diagnosis, negative hepatitis B serology, and access to a multidisciplinary health team. In the South, age below 40 years was associated with longer survival. O estudo objetivou avaliar o tempo de sobrevida de pacientes de AIDS, com 13 anos ou mais de idade, das regiões Sul e Sudeste do país, segundo características sóciodemográficas e clínico-epidemiológicas. A amostra foi sorteada a partir da totalidade dos casos notificados no Sistema de Vigilância Epidemiológica do Programa Nacional de DST/AIDS, diagnosticados em 1998 e 1999. Utilizando-se questionário foi possível analisar 2.091 prontuários médicos. Pelo método Kaplan-Meier, foi estimada sobrevivência de pelo menos 108 meses após o diagnóstico em 59,5% dos pacientes no Sudeste e 59,3% no Sul. Por meio de modelos de regressão de Cox, foi verificado, nas duas regiões, aumento da sobrevivência nos pacientes que usaram antirretrovirais, que foram classificados como caso de AIDS pelo critério CD4, que eram do sexo feminino e com maior escolaridade. Os fatores associados a tempos maiores de sobrevida no Sudeste foram ainda: possuir cor da pele branca, não ter tido tuberculose após seu diagnóstico de AIDS, não ser reagente à hepatite B e ter tido acesso à equipe multidisciplinar. No Sul, ter idade abaixo de 40 anos possibilitou maior sobrevida.